Causal role of immune cells in chronic periodontitis: a bidirectional Mendelian randomization study - Yu Chen; Xinyang Jin; Qi Wang; Sai Hu; Xu Huang (BMC, 2024)
Abstract Background This study aims to explore the bidirectional causal relationship between immune cell phenotypes and chronic periodontitis using a Mendelian randomization framework. Materials and methods Through a two-sample Mendelian randomization analysis, this research examined genetic data related to 731 immune cell traits and chronic periodontitis. Instrumental variables were chosen based on their genetic links to either immune traits or periodontitis. Various statistical techniques, including MR-Egger regression, weighted median, and inverse-variance weighted (IVW) analysis, were employed to determine the causal connections. Results Predominantly using the IVW method, 26 distinct immune phenotypes were identified as potentially influencing periodontitis (P < 0.05). Conversely, periodontitis potentially affected 33 different immune phenotypes (P < 0.05). The results for pleiotropy and sensitivity tests were stable. However, these associations lost significance after adjusting for the False Discovery Rate. Conclusion This study uncovers a complex bidirectional causal relationship between certain immune cell phenotypes and chronic periodontitis, underscoring the intricate interaction between the immune system and the pathogenesis of periodontal disease.